2020
DOI: 10.1111/desc.13024
|View full text |Cite
|
Sign up to set email alerts
|

Contagious itching is heightened in children with autism spectrum disorders

Abstract: The authors tested susceptibility to contagious itching, laughter, and yawning in 55 children with autism spectrum disorder (ASD), ages 8–14, and 106 typically developing (TD) children, ages 5–14. Children with ASD were less likely to yawn or laugh contagiously compared with TD peers, but showed increased susceptibility to contagious itching, under naturalistic conditions. Contagious yawning and laughter were positively correlated with emotional empathy in the TD group. In contrast, contagious itching showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(122 reference statements)
4
7
1
Order By: Relevance
“…One previous study found that children with ASD showed heightened contagious itch compared with typically developing controls (Helt et al, 2020). The current study sheds light on a possible factor driving that relationship.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…One previous study found that children with ASD showed heightened contagious itch compared with typically developing controls (Helt et al, 2020). The current study sheds light on a possible factor driving that relationship.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, Massen and Gallup (2017) propose that contagious yawning is more linked to visual attention than to empathy. In addition, children with ASD have been shown to be more susceptible to itch contagion, which is a form of contagion not transmitted via the eyes (Helt et al, 2020). Scambler et al (2007) reported that when children with ASD paid attention to the emotional stimulus, they were just as likely to demonstrate an empathetic response.…”
Section: Contagion In Psychopathy and Asdmentioning
confidence: 99%
“…Hence, mimicry is not considered binomial (0-1) but is a cumulative variable that allows for more than one mimicry instance (minimum: 0; maximum observed in the current study: 2). Based on previous studies, we selected a time window of 30seconds to count mimicry, being 30-seconds on average between the time window usually reported for scratch (~5-10s) and yawn (~60-90) contagion (59,87). Since this 30-second boundary is admittedly slightly arbitrary and since there is also no complete agreement in the literature (59,(88)(89)(90), we verified that our results hold when using a different time boundary (Supplementary material).…”
Section: Discussionsupporting
confidence: 64%
“…Our behavioural data reveal that children with ASC did indeed copy their interaction partner's gestures less frequently than did their NT peers. This finding adds to a growing body of research, which has showed altered mimicry of facial expressions presented to ASC participants on computer screens (Helt et al, 2020;Oberman et al, 2009;Senju et al, 2007) and of gestures performed during live interactions (Helt et al, 2010). Importantly, our interaction task was designed to be naturalistic, and yet, not biased towards NT interactions, which are characterised by coordinated exchanges such as mutual eye gaze and turn-taking (Akhtar & Jaswal, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…Impairments in spontaneous mimicry of facial expressions (Oberman, Winkielman, & Ramachandran, 2009), yawning (Helt, Eigsti, Snyder, & Fein, 2010;Senju et al, 2007) and body movements (K. L. have been widely reported in ASC. While these impairments often involve reduced mimicry in ASC, a recent study (Helt et al, 2020) has shown that increased mimicry can also be related to autism severity, especially when the actions involve negatively-valenced stimuli that may evoke personal distress (e.g., contagious itching as if sand is in one's hair or clothes). Studies also show robust autism-associated impairments in copying the style of an action (Hobson & Hobson, 2008) or copying actions that are irrelevant to attaining a goal, such as tapping the lid of a box before opening it (Marsh, Pearson, Ropar, & Hamilton, 2013).…”
Section: Mimicry Behaviour and Autismmentioning
confidence: 99%